Coronavirus disease 2019 (COVID‐19)–related smell and taste impairment with widespread diffusion of severe acute respiratory syndrome–coronavirus‐2 (SARS‐CoV‐2) Omicron variant - Boscolo‐Rizzo, Paolo; Tirelli, Giancarlo; Meloni, Pierluigi; Hopkins, Claire; Madeddu, Giordano; De Vito, Andrea; Gardenal, Nicoletta; Valentinotti, Romina; Tofanelli, Margherita; Borsetto, Daniele; Lechien, Jerome R.; Polesel, Jerry; et al. (International forum of allergy & rhinology, 2022)
Background The aim of this study was to estimate the prevalence of self‐reported chemosensory dysfunction in a study cohort of subjects who developed a mild‐to‐moderate coronavirus disease 2019 (COVID‐19) in the period from January 17, 2022, to February 4, 2022 (Omicron proxy period) and compared that with a historical series of patients testing positive for severe acute respiratory syndrome–coronavirus‐2 (SARS‐CoV‐2) infection between March and April, 2020 (comparator period). Methods Prospective study based on the 22‐item Sino‐Nasal Outcome Tool (SNOT‐22), item “sense of smell or taste” and additional outcomes. Results Patients’ characteristics and clinical presentations of COVID‐19 were evaluated and compared in 779 patients, 338 of the study cohort and 441 of the historical series. The prevalence of self‐reported chemosensory dysfunction during the proxy Omicron period (32.5%; 95% confidence interval [CI], 27.6–37.8) was significantly lower from that during the comparator period (66.9%; 95% CI, 62.3–71.3) (p < 0.001). Nearly one‐quarter of patients (24.6%; 95% CI, 20.1–29.5) reported an altered sense of smell during the proxy Omicron period compared to 62.6% (95% CI, 57.9–67.1) during the comparator period (p < 0.001). Similarly, the prevalence of an altered sense of taste dropped to 26.9% (95% CI, 22.3–32.0) during the proxy Omicron period from 57.4% (95% CI, 52.6–62.0) during the comparator period (p < 0.001). The severity of chemosensory dysfunction was lower in the proxy Omicron period compared to the comparator period (p < 0.001). Conclusion The prevalence and the severity of COVID‐19–associated smell and taste dysfunction has dropped significantly with the advent of the Omicron variant but it still remains above 30%.